Effect of seasonal variation and supplementation on yield of oyster mushrooms cultivated on indigenous grasses in Botswana - Jongman, M; Khonga, E B; Khare, K B; John, T Mubyana (Mushroom Research, 2010)
A hybrid of Pleurotus ostreatus x Pleurotus florida   was cultivated in a low technological mushroom house at Botswana College of Agriculture, Sebele. This oyster mushroom was   grown on maize cobs, Cenchrus cilliairs, Eragrostis pallens and Phragmites sp. un-supplemented or supplemented with wheat bran, gram flour and cowpea pods. The experiment was carried out over two seasons, winter and summer. The yield and BE (Biological efficiency) of the mushroom on Cenchrus cilliaris was the highest in all seasons. In summer trials the incubation period was lower and BE higher in all substrates than winter trials. The BE on un-supplemented C. cilliaris in summer and winter were 79.33% and 74.33%, respectively while supplemented with cowpea pods were 87.73% and 82.07% in summer and winter, respectively. The incubation period and BE on maize cobs supplemented with wheat bran in summer were 18.67 days and 78.6%, respectively. The yield on Eragrostis pallens (BE) supplemented with gram flour was the lowest in summer while the yield on un-supplemented Phragmites sp. was the lowest (63.3%) among all trials.